2021
DOI: 10.3390/pharmaceutics13101644
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as a New Delivery Vehicle in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a type of chronic relapsing inflammatory disease. The pathogenesis of IBD is still unclear, which may involve environmental factors, genetic factors, intestinal microbiota disorder, and abnormal immune responses. Exosomes (30–150 nm) are found in various body fluids, including blood, saliva, urine, and cerebrospinal fluid. Exosomes mediate intercellular communication and regulate cell biological activity by carrying non-coding RNAs, proteins, and lipids. There is evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…As an emerging alternative cell-free therapy in various diseases including IBD, MSC-Ex potently reduces the expression of pro-inflammatory cytokines such IFN-γ, TNF-α, and IL-1β, and increases the secretion of anti-inflammatory cytokines TGF-β1 and IL-10. 17,18 A recent study by our research team demonstrated that human umbilical cord mesenchymal stem cell (hucMSC)-derived exosomes inhibit the activation of NLRP3 inflammasomes and other key pro-inflammatory cytokines in the mouse colon of DSS-induced colitis. 19 These findings are consistent with the current study that found that MSC-Ex significantly reduced the expression of pro-inflammatory cytokines such as IL-1β, IL-6, and TNFα but increased the anti-inflammatory cytokine, IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…As an emerging alternative cell-free therapy in various diseases including IBD, MSC-Ex potently reduces the expression of pro-inflammatory cytokines such IFN-γ, TNF-α, and IL-1β, and increases the secretion of anti-inflammatory cytokines TGF-β1 and IL-10. 17,18 A recent study by our research team demonstrated that human umbilical cord mesenchymal stem cell (hucMSC)-derived exosomes inhibit the activation of NLRP3 inflammasomes and other key pro-inflammatory cytokines in the mouse colon of DSS-induced colitis. 19 These findings are consistent with the current study that found that MSC-Ex significantly reduced the expression of pro-inflammatory cytokines such as IL-1β, IL-6, and TNFα but increased the anti-inflammatory cytokine, IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…135 Furthermore, exosomes have unique advantageous characteristics, such as low immunogenicity and biodegradability, high biocompatibility and load capacity, and small size, making them suitable as drugs vehicles to treat human diseases, including IBD. [136][137][138][139] For example, G. J. Wang et al have demonstrated that human umbilical cord mesenchymal stromal cell (hucMSC)-derived exosomal cargo miR-316, as an anti-inflammatory factor, can relieve experimental mouse colitis by inhibiting the neddylation of NEDD8, and inactivating the NF-kB signaling pathway. 140 Additionally, bone marrow mesenchymal stem cell (BMSC)-derived exosome encapsulated miR-146a, a well-known anti-inflammatory molecular, can apparently decrease the levels of the inflammatory cytokines, such as TNF-a, IL-6, and IL-1b, and attenuate inflammation in 2,4,6trinitrobenzene sulfonic acid (TNBS)-induced colitis by suppressing activation of NF-kB pathway.…”
Section: Exosomesmentioning
confidence: 99%
“…105 Recently, exosomes can be used as biomarkers and indicators in diagnosing diseases, including IBD, due to their extensive existence in the above-mentioned biological fluids. 30,[106][107][108] Shao et al have reported that a serum exosome, pregnancy zone protein (PZP), is up-regulated in the IBD patients, and can be regarded as a promising biomarker of serological detection for IBD diagnosis. 108 Zhang et al have indicated that a salivary exosome, proteasome subunit alpha type 7 (PSMA7), is present at high levels in IBD patients and may be a promising indicator for IBD diagnosis.…”
Section: Exosomes In Body Fluidsmentioning
confidence: 99%